IMPLIKASI PENGEMBANGAN KARYAWAN TERHADAP PRODUKTIVITAS KERJA: STUDI PADA KARYAWAN BANK BTPN CABANG SUNGGUMINASA - Mutmainna Rachman; Rini (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2024)
This study aims to determine the effect of employee development on work productivity at PT. Bank BTPN, Sungguminasa, Gowa Regency. Employee development is one of the factors that can influence the level of work productivity. Employee development in this context is not limited to an additional base salary, but also includes skill enhancement and recognition for specific achievements or expertise. However, development may not be effective if it solely focuses on the completion of administrative tasks, such as reports or receipts, within a short period. This research employed simple linear regression analysis, the R² test, and the t-test to analyze the relationship between variables. The regression results show that the coefficient for employee development is 0.458, indicating that the employee development variable (X) has a positive effect on work productivity by 45.8%. Based on the t-test results, the t-calculated value was 3.524, with a significance level of 0.001 (< 0.05), while the t-table value was 2.042. Thus, it can be concluded that Ho is rejected and Ha is accepted, meaning that employee development (X) has a significant effect on work productivity.